2016
DOI: 10.1103/physrevb.94.245105
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic meaning of local temperature of nonequilibrium open quantum systems

Abstract: Measuring the local temperature of nanoscale systems out of equilibrium has emerged as a new tool to study local heating effects and other local thermal properties of systems driven by external fields. Although various experimental protocols and theoretical definitions have been proposed to determine the local temperature, the thermodynamic meaning of the measured or defined quantities remains unclear. By performing analytical and numerical analysis of bias-driven quantum dot systems both in the noninteracting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 68 publications
1
32
0
Order By: Relevance
“…Such a minimal perturbation condition (MPC) can be examined by monitoring the evolution of a certain thermosensitive property of the system [140]. As a consequence, operational protocols based on the MPC have been proposed, with which the local temperature can be determined quantitatively by presuming the local equilibrium approximation [182,183].…”
Section: General Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a minimal perturbation condition (MPC) can be examined by monitoring the evolution of a certain thermosensitive property of the system [140]. As a consequence, operational protocols based on the MPC have been proposed, with which the local temperature can be determined quantitatively by presuming the local equilibrium approximation [182,183].…”
Section: General Remarksmentioning
confidence: 99%
“…1.3) may become independent of each other. For instance, it is difficult to define a unique local temperature if nonlocal excitations emerge in the system [183]. Second, the practical implementation of a theoretical definition may involve non-universal approximation or parametrization procedure.…”
Section: Uniqueness/non-uniqueness Of Local Temperature Out Of Equilimentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical implementation of the HEOM formalism, usually termed HEOM, can capture the combined effects of system-reservoir dissipation, many-body interactions, and non-Markovian memory in a nonperturbative manner. The HEOM approach is applicable to both static and dynamic properties of diverse quantum impurity systems [55][56][57][58][59][60][61][62][63][64][65]. Moreover, it has also been combined with the density-functional theory to study the correlated electronic structure of adsorbed magnetic molecules [66][67][68].…”
Section: The Heom Approachmentioning
confidence: 99%
“…From the same standpoint, thermal transport studies were conceived and came to be conclusive in the upcoming years [2]. Subsequently, several theoretical studies demonstrated the possibility to conduct both thermal and charge through tunneling junctions [26][27][28][29][30][31][32][33][34], both in presence and absence of lattice vibrations, although there is no generic framework that successfully is capable of describing the thermodynamic properties of nano junctions [8,14,35].…”
Section: Introductionmentioning
confidence: 99%